Alkane hydroisomerization catalyst and preparation method and application thereof

By controlling the spatial distance and surface element molar ratio of the AOx/BOy components in the catalyst, the hydrogen spillover effect is enhanced, solving the problem of low reaction activity of existing catalysts and realizing a low-temperature and high-efficiency alkane isomerization reaction.

CN121016735APending Publication Date: 2025-11-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410665949.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

In existing alkane isomerization catalysts, the hydrogen spillover effect is not obvious, resulting in low reaction activity. This requires higher noble metal loading and reaction temperature, which increases economic and operating costs.

Method used

Catalysts employing AOx/BOy, M/Al2O3, and molecular sieve components, by controlling the spatial distance between AOx and BOy in the range of 20.0-150.0 nm and optimizing the molar ratio of A and B elements on the catalyst surface to 0.13-0.40, synergistic effects are achieved, enhancing the hydrogen spillover effect and reducing the reaction energy barrier.

Benefits of technology

The reaction temperature for isomerization was significantly reduced, with the optimal yield of the isomers reduced to 240°C, thus improving economic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004861094620000121
    Figure BDA0004861094620000121
  • Figure BDA0004861094620000131
    Figure BDA0004861094620000131
Patent Text Reader

Abstract

The invention discloses an alkane hydroisomerization catalyst and a preparation method and application thereof. The catalyst comprises an AOx / BOy component, an M / Al2O3 component and a molecular sieve component, wherein AOx in the AOx / BOy component is one or more of TiO2, ZnO, Cr2O3, MgO, Fe2O3 and Co2O3, x is a positive integer, BOy is one or more of ZrO2, MnO2, MoO3 and WO3, and y is a positive integer; m in the M / Al2O3 component is one or more of Pt, Pd, Rh, Ru and Ir elements; in the AOx / BOy component, the spatial distance between AOx and BOy is controlled to be 20.0-150.0 nm. The catalyst provided by the invention is used in an alkane hydroisomerization reaction, and the reaction temperature is obviously reduced when the optimal isomer yield is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of alkane isomerization reaction, specifically relating to an alkane hydroisomerization catalyst, its preparation method, and its application. Background Technology

[0002] With increasing environmental protection requirements, there will be significant demand in the future for high-quality isomerized oil blending components with efficient and selective synthesis of low-sulfur, low-olefin, and low-aromatic content. Based on the metal-acid dual-center synergistic catalytic reaction process, the isomerization reaction of n-alkanes can selectively generate high-octane isoalkanes from low-octane n-alkanes. Michel Guisnet's research (GUISNET M. “Ideal” bifunctional catalysis over Pt-acid zeolites[J]. Catalysis Today,2013,218-219:123-134.) shows that this process follows a typical bifunctional synergistic catalytic reaction mechanism. In an ideal isomerization reaction, n-alkanes first undergo dehydrogenation at the metal to generate n-olefins. Subsequently, the n-olefins diffuse to the acidic sites of the molecular sieve and undergo skeletal isomerization to generate isoolefin intermediates. These intermediates then return to the metal sites for hydrogenation to generate the target product, the isoalkane. Metal active sites are typically provided by noble metals such as Pt and Pd, primarily used for hydrogen dissociation, alkane dehydrogenation, and subsequent olefin intermediate hydrogenation. To improve the utilization efficiency of metal centers and reduce catalyst production costs, researchers generally focus on three aspects: enhancing noble metal dispersion, designing noble metal-non-noble metal alloy structures, and developing highly active non-noble metal systems. On the other hand, during hydrogenation-dehydrogenation reactions, hydrogen species generated at the metal active sites can migrate to adjacent oxide surfaces or metal-oxide interfaces, resulting in hydrogen spillover. Enhancing this hydrogen spillover phenomenon helps optimize the reaction pathway and lower the reaction energy barrier.

[0003] Jovana Zecevic's research group (Nanoscale intimacy in bifunctional catalysts for selective conversion of hydrocarbons. Nature. 2015, 528: 245-248) investigated a class of catalysts (Pt-on-Al2O3) that ensures that acidic sites inside the molecular sieve channels are in nanoscale contact. In this case, the olefin intermediates formed during the reaction preferentially undergo "pore-mouth catalysis," thereby maximally suppressing the cracking process of the intermediates within the micropores of the molecular sieve and achieving efficient synthesis of the target product isomers. However, in this type of catalyst, the Pt metal sites are located on the alumina binder (Pt / Al2O3). The inertness of alumina leads to a weak hydrogen spillover effect during the reaction, resulting in low reactivity at low temperatures. To obtain the optimal isomer yield, a higher loading of Pt metal and a higher reaction temperature are still required, increasing economic and operating costs. Therefore, how to enhance the hydrogen spillover effect in this type of system is an urgent problem to be solved. Summary of the Invention

[0004] To address the aforementioned problems, this invention provides an alkane hydroisomerization catalyst, its preparation method, and its applications. The alkane isomerization catalyst of this invention achieves the optimal yield of the desired isomer at a significantly lower reaction temperature during the hydroisomerization reaction of n-alkanes.

[0005] The first aspect of this invention provides an alkane hydroisomerization catalyst, the catalyst comprising AO x / BO y Components, M / Al2O3 components and molecular sieve components; among which, AO x / BO y AO in the components x It is one or more of TiO2, ZnO, Cr2O3, MgO, Fe2O3, and Co2O3, where x is a positive integer, and BO y The M / Al2O3 component contains one or more of ZrO2, MnO2, MoO3, and WO3, where y is a positive integer; M in the M / Al2O3 component contains one or more of Pt, Pd, Rh, Ru, and Ir elements, preferably Pt; AO x / BO y In the components, AO x and BO y The spatial distance is controlled within 20.0 to 150.0 nm, preferably 20.0 to 100.5 nm.

[0006] Furthermore, AO x and BO ySpatial distance is represented by the shortest line connecting any point on the outer edge of region A and any point on the outer edge of region B, as determined by STEM-EDX technology.

[0007] Further, preferably, AO x / BO y AO in the components x It is one or more of TiO2 and ZnO, where x is a positive integer, and BO y It is one or more of ZrO2, MnO2, and MoO3, and y is a positive integer.

[0008] Furthermore, based on catalyst mass, AO x / BO y The content of the component is 5.0 wt% to 35.0 wt%, the content of M / Al2O3 component is 20.0 wt% to 60.0 wt%, and the content of molecular sieve component is 20.0 wt% to 60.0 wt%.

[0009] Furthermore, based on the mass of the catalyst, the content of M in component M / Al2O3, calculated as a metal element, is 0.01wt% to 10.0wt%, preferably 0.1wt% to 2.5wt%. For example, but not limited to, 0.1wt%, 0.2wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2.0wt%, 2.4wt%, 2.5wt%, and any range between any two values.

[0010] Furthermore, AO x / BO y In the components, oxide AO x and oxide BO y The mass ratio is 0.05 to 1.0, preferably 0.2 to 1.0.

[0011] Furthermore, the molar ratio X of element A and element B on the catalyst surface is 0.13 to 0.40, preferably 0.23 to 0.40.

[0012] Furthermore, in the M / Al2O3 component, the pore volume of the alumina is 0.30–0.75 mL / g, preferably 0.45–0.70 mL / g.

[0013] Furthermore, the molecule is screened from at least one of ZSM-5, ZSM-11, ZSM-22, ZSM-35, Beta, MOR, and Y, preferably at least one of ZSM-5, ZSM-11, and ZSM-22.

[0014] Furthermore, the molecular sieve has a SiO2 / Al2O3 molar ratio of 20–250 and a specific surface area of ​​200–620 m². 2 / g, pore volume is 0.11~0.92cm 3 / g.

[0015] In a second aspect, the present invention provides a method for preparing an alkane hydroisomerization catalyst, comprising the following steps:

[0016] (1) AO x BO y Mix with water (preferably deionized water), and heat treat to obtain AO. x / BO y Components;

[0017] (2) Metal M is loaded onto alumina to obtain the M / Al2O3 composition;

[0018] (3) Take the AO obtained in step (1) x / BO y The components and the M / Al2O3 component obtained in step (2) are mixed and heat-treated to obtain AO. x / BO y A mixture of components and M / Al2O3 components;

[0019] (4) The mixture obtained in step (3) is mixed with molecular sieve to obtain the alkane hydroisomerization catalyst.

[0020] Furthermore, in step (1), AO x It is one or more of TiO2, ZnO, Cr2O3, MgO, Fe2O3, and Co2O3, preferably one or more of TiO2 and ZnO, where x is a positive integer, and BO y It is one or more of ZrO2, MnO2, MoO3, and WO3, preferably one or more of ZrO2, MnO2, and MoO3, where y is a positive integer.

[0021] Further, in step (1), AO is measured by mass. x and BO y The mixing ratio is 0.05 to 1.0, preferably 0.2 to 1.0.

[0022] Further, in step (1), AO x and BO y The mixture was placed in deionized water, stirred until homogeneous, dried, and then heat-treated to obtain AO. x / BO yComponents. The heat treatment temperature is 250–500℃, preferably 350–500℃, and the treatment time is 0.5h–24h, preferably 4h–12h.

[0023] Furthermore, in step (2), the metal M is one or more of the elements Pt, Pd, Rh, Ru, and Ir, preferably Pt.

[0024] Further, preferably, in step (2), the loading is carried out by adding a precursor solution containing metal M dropwise to a suspension of alumina for reaction.

[0025] Further, the concentration of metal M in the precursor solution is 0.001 mg M / mL to 2.50 mg M / mL, preferably 0.1 mg M / mL to 1.5 mg M / mL. Preferably, in the precursor solution containing metal M, the precursors of Pt, Pd, Rh, Ru, and Ir are one or more of chloroplatinic acid, chloropalladium acid, rhodium chloride, ruthenium trichloride, pentaammonium chloride dichloride, and iridium tetrachloride. Preferably, the pH value of the alumina suspension is 0.5 to 3.5.

[0026] Further, the preparation process of the alumina suspension is as follows: alumina is mixed with water, and after a first stirring, material I is obtained; the pH value of material I is adjusted, and after a second stirring, an alumina suspension is obtained. Preferably, the first stirring time is 0.1–1.0 h; the second stirring time is 0.5–2.0 h. Preferably, hydrochloric acid is slowly added dropwise to material I to adjust the pH value to 0.5–3.5. Preferably, the alumina is γ-alumina. The pore volume of the alumina is 0.30–0.75 mL / g, preferably 0.45–0.70 mL / g.

[0027] Further, the reaction time is 0.5–10.5 h. After the reaction is complete, the mixture is first filtered, washed, and dried, then heat-treated to obtain the M / Al2O3 component. The filtration and washing can be performed using conventional methods in the art. The drying conditions are as follows: temperature 40–120 °C, time 2–15 h. The heat treatment conditions are as follows: treatment temperature 350–600 °C, preferably 450–500 °C, treatment time 0.5 h–24 h, preferably 4 h–12 h.

[0028] Furthermore, in step (3), AO is measured by mass. x / BO y The mass ratio of the component to the M / Al2O3 component is 1:9 to 7:10.

[0029] Furthermore, in step (3), the mixing is a physical mixing, and the mixing method includes grinding, ball milling, etc.

[0030] Further, in step (3), the heat treatment is carried out under hydrogen-containing conditions. The hydrogen-containing conditions are that the hydrogen volume content is 5% to 100%, preferably 50% to 100%, and the inert gas used is the balance gas, which is one or more of N2, Ar, and He.

[0031] Further, in step (3), the heat treatment conditions are: temperature 350-500℃, preferably 450-500℃, and treatment time 0.5h-24h, preferably 4h-12h.

[0032] Further, in step (4), the mass ratio of the mixture obtained in step (3) to the molecular sieve component is 1:9 to 9:1. Further, the molecular sieve is selected from at least one of ZSM-5, ZSM-11, ZSM-22, ZSM-35, Beta, MOR, and Y, preferably at least one of ZSM-5, ZSM-11, and ZSM-22. Preferably, the molecular sieve has a SiO2 / Al2O3 molar ratio of 20 to 250 and a specific surface area of ​​200 to 620 m². 2 / g, pore volume is 0.11~0.92cm 3 / g.

[0033] Furthermore, in step (4), the mixing is a physical mixing, and the mixing method includes any one of grinding, ball milling, etc.

[0034] Furthermore, the resulting catalyst includes AO x / BO y Components, M / Al2O3 components and molecular sieve components, the AO x / BO y In the components, AO x and BO y The spatial distance is controlled within 20.0-150.0 nm, preferably 20.0-100.5 nm.

[0035] Furthermore, based on catalyst mass, AO x / BO y The content of the component is 5.0 wt% to 20.0 wt%, the content of the M / Al2O3 component is 20.0 wt% to 60.0 wt%, and the content of the molecular sieve component is 20.0 wt% to 60.0 wt%.

[0036] Furthermore, based on the mass of the catalyst, the content of M in component M / Al2O3, calculated as a metal element, is 0.01wt% to 10.0wt%, preferably 0.1wt% to 2.5wt%.

[0037] Furthermore, AO x / BO yIn the components, oxide AO x and oxide BO y The mass ratio is 0 to 0.8, preferably 0.2 to 0.6.

[0038] Furthermore, the molar ratio X of element A and element B on the catalyst surface is 0.13 to 0.40, preferably 0.23 to 0.40.

[0039] A third aspect of the invention also provides the application of the above-described catalyst in the catalytic isomerization reaction of alkane.

[0040] Furthermore, the alkane is at least one of the n-alkanes having 4 to 8 carbon atoms (e.g., at least one of n-pentane, n-hexane, n-heptane, and n-octane).

[0041] Further, the preferred conditions for the alkane isomerization reaction are: a reaction temperature of 200–405°C, preferably 230–280°C; a reaction pressure of 1.0–3.0 MPa; a molar ratio of hydrogen to n-alkane of 1.0–10.0; and a mass hourly space velocity (HSV) of alkane of 1.0–8.0 h⁻¹. -1 .

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] This invention provides a novel alkane hydroisomerization catalyst, which comprises AO x / BO y Components, M / Al2O3 components and molecular sieve components, of which AO x and BO y The spatial distance is controlled between 20.0 and 150.0 nm. Furthermore, the molar ratio of element A to element B on the surface of the catalyst of the present invention is between 0.13 and 0.40. The two elements work synergistically. When the catalyst of the present invention is applied to the hydrogenation isomerization reaction of C4-C8 n-alkanes, it is beneficial to the formation of isomerization products and has high selectivity and yield of isomer products.

[0044] The inventors discovered through research that by controlling AO x / BO y The proportions, heat treatment conditions, and subsequent synthesis conditions can affect AO x / BO y The interaction between the oxide and the support in the component is microscopically regulated. When AO x and BO yBy controlling the spatial distance to 20.0-150.0 nm, a better hydrogen-rich microenvironment is provided for the isomerization reaction, thus enhancing hydrogen spillover. Furthermore, by adjusting the molar ratio X of elements A and B on the catalyst surface to 0.13-0.40, their synergistic effect further strengthens the hydrogen spillover effect in the reaction. Through comprehensive coordination of each preparation step, this invention significantly reduces the energy barrier of the isomerization reaction and substantially lowers the reaction temperature for achieving the optimal conformation yield, thereby improving economic efficiency.

[0045] The catalyst of this invention is used in the hydroisomerization reaction of low-carbon alkanes to achieve the optimal yield of isomers (Yma). x The required reaction temperature (Tma) at 75.1% x It can be reduced to 240℃. Detailed Implementation

[0046] To more clearly illustrate the technical solution of the present invention, the following specific embodiments are listed. However, those skilled in the art will readily understand that the description of the embodiments is for illustrative purposes only and should not, and will not, limit the invention as described in detail in the claims.

[0047] In this invention, the molar ratio X of elements A and B on the catalyst surface was measured by X-ray photoelectron spectroscopy (XPS). The spectra were calibrated using a Kratos Analytical AXIS Ultra DLD spectrometer with the C1s peak binding energy of 284.6 eV as the standard.

[0048] In this invention, AOx and BO y Spatial distances were measured using STEM-EDX technology with an instrument model of FEI TitanCubedThemis G2 and an accelerating voltage of 300kV. EDX testing was performed using an Aztec X-Max 100TLE instrument from Oxford Instruments. During the testing process, at a 1-micron scale, the spatial distribution of metals A and B was analyzed using STEM-EDX technology. Regions A and B were identified separately. The shortest distance between regions A and B was calculated by taking the shortest line connecting any point on the outer edge of region A to any point on the outer edge of region B. After more than 20 measurements, the average distance was calculated to obtain the average distance between regions A and B, namely AOx and BO. y Spatial distance.

[0049] The relevant parameters of the ZSM-5 molecular sieve powder used in this invention are as follows: SiO2 / Al2O3 = 25 (molar ratio), specific surface area (S) BET ) = 425m 2 / g, pore volume = 0.12cm 3 / g.

[0050] The relevant parameters of the ZSM-22 molecular sieve powder used in this invention are as follows: SiO2 / Al2O3 = 40 (molar ratio), specific surface area (S) BET ) = 500m 2 / g, pore volume = 0.21cm 3 / g.

[0051] In this invention, the relevant parameters of the β-molecular sieve raw powder used are as follows: SiO2 / Al2O3 = 28 (molar ratio), specific surface area (S) BET ) = 205m 2 / g, pore volume = 0.25cm 3 / g.

[0052] In this invention, the alumina crystal form used is γ-type, with a specific surface area of ​​475 m². 2 / g, pore volume = 0.25cm 3 / g.

[0053] In this invention, the reaction products were analyzed using an Agilent 7890B gas chromatograph.

[0054] In this invention, the formulas for calculating conversion rate and isomer selectivity are as follows:

[0055] Conversion rate = 1 - (mass of isohexane in reactants / mass of n-hexane in feed) × 100%;

[0056] Isomer selectivity = (mass of isohexane in product / total mass of product) × 100%;

[0057] Yield = Conversion rate × Selectivity × 100%.

[0058] Comparative Example 1

[0059] (1) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 40mL of 0.5mg hydrochloric acid dropwise. P A solution of H2PtCl6·6H2O with a concentration of t / mL was stirred for 3 hours, filtered, and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 hours, and then air-treated at 500 °C for 6 hours to obtain the Pt / Al2O3-D1 component.

[0060] (2) Mix 1g of Pt / Al2O3-D1 component with 1g of ZSM-5 molecular sieve powder and grind to obtain catalyst D1. By mass, the catalyst contains 0.5% Pt, 49.5% alumina, and 50% molecular sieve.

[0061] Comparative Example 2

[0062] (1) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 40mL of 0.5mg hydrochloric acid dropwise. P A solution of H2PtCl6·6H2O with a concentration of t / mL was stirred for 3 hours, filtered, and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 hours, and then air-treated at 500 °C for 6 hours to obtain the Pt / Al2O3-D2 component.

[0063] (2) 2.0 g Pt / Al2O3-D2, 0.1 g TiO2, 0.5 g MnO2, and 1.4 g ZSM-5 molecular sieve were physically ground to obtain catalyst D2. By mass, the catalyst contained 0.5% Pt, 49.5% alumina, 15% TiO2 and MnO2, and 35% molecular sieve. The molar ratio of Ti to Mn elements on the catalyst surface was determined using XPS, as shown in Table 1.

[0064] Comparative Example 3

[0065] (1) Preparation of ZnZrOx by coprecipitation: 5.5 g Zr(NO3)4·5H2O and 7.3 g Zn(NO3)2·6H2O were added to 300 g deionized water and stirred evenly. Then, the mixture was placed in a 70 °C water bath, and 1 mol / L ammonium bicarbonate solution was added dropwise while stirring to adjust the pH to 6.5. After aging at 80 °C for two hours, the mixture was filtered and washed with 1.5 L of deionized water. The resulting filter cake was dried in a 100 °C oven for 12 h, and then air-treated at 500 °C for 6 h to obtain ZnZrOx. x -D3;

[0066] (2) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 40mL of 0.5mg hydrochloric acid dropwise. P A solution of H2PtCl6·6H2O with a concentration of t / mL was stirred for 3 hours, filtered, and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 hours, and then air-treated at 500 °C for 6 hours to obtain the Pt / Al2O3-D3 component.

[0067] (3) Mix 2g of Pt / Al2O3-D3 component with 0.4g of ZnZrOx-D3, grind, and treat with pure H2 at 450℃ for 6h to obtain Pt / Al2O3+ZnZrO x -D3 component;

[0068] (4) Mix 0.96g of Pt / Al2O3+ZnZrOx-D3 with 1.04g of ZSM-5 molecular sieve powder, grind, and obtain catalyst D3. By mass, the catalyst contains 0.5% Pt, 39.5% alumina, and 1.04g ZnZrOx-D3. x The D3 content is 8%, and the molecular sieve content is 52%. The molar ratio of Zn and Zr elements on the catalyst surface was determined using XPS characterization, as shown in Table 1.

[0069] Comparative Example 4

[0070] (1) Preparation of ZnZrOx by ammonia distillation: 5.5 g Zr(NO3)4·5H2O and 7.3 g Zn(NO3)2·6H2O were added to 300 g deionized water and stirred until homogeneous. Then, 25 wt% ammonia solution was added dropwise under stirring at room temperature (25℃) to adjust the pH to 11. After stirring for 2 h, the mixture was refluxed at 80℃ for 24 h. After cooling to room temperature (25℃), the mixture was filtered and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100℃ for 12 h, and then air-treated at 500℃ for 6 h to obtain ZnZrOx. x -D4;

[0071] (2) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 40mL of 0.5mg hydrochloric acid dropwise. P A solution of H2PtCl6·6H2O with a concentration of t / mL was stirred for 3 hours, filtered, and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 hours, and then air-treated at 500 °C for 6 hours to obtain the Pt / Al2O3-D4 component.

[0072] (3) Mix 2g of Pt / Al2O3-D4 component with 0.4g of ZnZrOx-D4, grind, and treat with pure H2 at 450℃ for 6h to obtain Pt / Al2O3+ZnZrO x -D4 component;

[0073] (4) Mix 0.96g of Pt / Al2O3+ZnZrOx-D4 with 1.04g of ZSM-5 molecular sieve powder, grind, and obtain catalyst D4. By mass, the catalyst contains 0.5% Pt, 39.5% alumina, and 1.04g ZnZrOx-D4. x The D4 content is 8%, and the molecular sieve content is 52%. The molar ratio of Zn and Zr elements on the catalyst surface was determined using XPS characterization, as shown in Table 1.

[0074] Comparative Example 5

[0075] (1) Mix 0.1g TiO2 and 10g MnO2 in 50mL of deionized water, stir for 6h, filter and wash, and then air treat at 500℃ for 6h to obtain TiO2 / MnO2-D5;

[0076] (2) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 40mL of 0.5mg hydrochloric acid dropwise. P A solution of H2PtCl6·6H2O with a concentration of t / mL was stirred for 3 hours, filtered, and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 hours, and then air-treated at 500 °C for 6 hours to obtain the Pt / Al2O3-D5 component.

[0077] (3) 2g of Pt / Al2O3-D5 component and 0.4g of TiO2 / MnO2-D5 were physically ground and treated with pure H2 at 450℃ for 6h to obtain Pt / Al2O3+TiO2 / MnO2-D5 component;

[0078] (4) 0.96 g of Pt / Al2O3+TiO2 / MnO2-D5 was mixed with 1.04 g of ZSM-5 molecular sieve powder and ground to obtain catalyst D5. By mass, the catalyst contained 0.5% Pt, 39.5% alumina, 8% TiO2 / MnO2, and 52% molecular sieve. The molar ratio of Ti and Mn elements on the catalyst surface was determined using XPS characterization, as shown in Table 1.

[0079]

Example 1

[0080] (1) Mix 2g TiO2 and 10g MnO2 in 50mL of deionized water, stir for 6h, filter and wash, and then air treat at 500℃ for 6h to obtain TiO2 / MnO2-S1;

[0081] (2) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 40mL of 0.5mg hydrochloric acid dropwise. P A solution of H2PtCl6·6H2O with a concentration of t / mL was stirred for 3 hours, filtered, and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 hours, and then air-treated at 500 °C for 6 hours to obtain the Pt / Al2O3-S1 component.

[0082] (3) 2g of Pt / Al2O3-S1 component and 0.4g of TiO2 / MnO2-S1 were physically ground and treated with pure H2 at 450℃ for 6h to obtain Pt / Al2O3+TiO2 / MnO2-S1 component;

[0083] (4) 0.96 g of Pt / Al2O3+TiO2 / MnO2-S1 was mixed with 1.04 g of ZSM-5 molecular sieve powder and ground to obtain catalyst S1. By mass, the catalyst contained 0.5% Pt, 39.5% alumina, 8% TiO2 / MnO2, and 52% molecular sieve. The molar ratio of Ti and Mn elements on the catalyst surface was determined using XPS, as shown in Table 1.

[0084]

Example 2

[0085] (1) Mix 1g TiO2 and 11g MnO2 in 50mL of deionized water, stir for 6h, filter and wash, and then air treat at 500℃ for 6h to obtain TiO2 / MnO2-S2.

[0086] (2) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 40mL of 0.5mg hydrochloric acid dropwise. P A solution of H2PtCl6·6H2O with a concentration of t / mL was stirred for 3 hours, filtered, and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 hours, and then air-treated at 500 °C for 6 hours to obtain the Pt / Al2O3-S2 component.

[0087] (3) 2g of Pt / Al2O3-S2 component and 0.4g of TiO2 / MnO2-S2 were physically ground and treated with pure H2 at 450℃ for 6h to obtain Pt / Al2O3+TiO2 / MnO2-S2 component;

[0088] (4) 0.96 g of Pt / Al2O3+TiO2 / MnO2-S2 was mixed with 1.04 g of ZSM-5 molecular sieve powder and ground to obtain catalyst S2. By mass, the catalyst contained 0.5% Pt, 39.5% alumina, 8% TiO2 / MnO2, and 52% molecular sieve. The molar ratio of Ti and Mn elements on the catalyst surface was determined by XPS characterization, as shown in Table 1.

[0089]

Example 3

[0090] (1) Mix 4g TiO2 and 8g MnO2 in 50mL of deionized water, stir for 6h, filter and wash, and then air treat at 450℃ for 6h to obtain TiO2 / MnO2-S3.

[0091] (2) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 40mL of 0.5mg hydrochloric acid dropwise. P A solution of H2PtCl6·6H2O with a concentration of t / mL was stirred for 3 hours, filtered, and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 hours, and then air-treated at 500 °C for 6 hours to obtain the Pt / Al2O3-S3 component.

[0092] (3) 2g of Pt / Al2O3-S3 component and 0.4g of TiO2 / MnO2-S3 were physically ground and treated with pure H2 at 450℃ for 6h to obtain Pt / Al2O3+TiO2 / MnO2-S3 component;

[0093] (4) 0.96g of Pt / Al2O3+TiO2 / MnO2-S3 was mixed with 1.04g of ZSM-5 molecular sieve powder and ground to obtain catalyst S3. By mass, the catalyst contained 0.5% Pt, 39.5% alumina, 8% TiO2 / MnO2, and 52% molecular sieve. The molar ratio of Ti and Mn elements on the catalyst surface was determined by XPS characterization, as shown in Table 1.

[0094]

Example 4

[0095] (1) Mix 2g ZnO and 10g MoO3 in 50mL of deionized water, stir for 6h, filter and wash, and then air treat at 500℃ for 6h to obtain ZnO / MoO3-S4.

[0096] (2) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 40mL of 0.5mg hydrochloric acid dropwise. P A solution of H2PtCl6·6H2O with a concentration of t / mL was stirred for 3 hours, filtered, and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 hours, and then air-treated at 500 °C for 6 hours to obtain the Pt / Al2O3-S4 component.

[0097] (3) 2g of Pt / Al2O3-S4 component and 0.4g of ZnO / MoO3-S4 were physically ground and treated with pure H2 at 450℃ for 6h to obtain Pt / Al2O3+ZnO / MoO3-S4 component;

[0098] (4) 0.96 g of Pt / Al2O3+ZnO / MoO3-S4 was mixed with 1.04 g of ZSM-22 molecular sieve powder and ground to obtain catalyst S4. By mass, the catalyst contained 0.5% Pt, 39.5% alumina, 8% ZnO / MoO3, and 52% molecular sieve. The molar ratio of Zn and Mo on the catalyst surface was determined using XPS characterization, as shown in Table 1.

[0099]

Example 5

[0100] (1) Mix 2g ZnO and 2g ZrO2 in 50mL of deionizer, stir for 6h, filter and wash, and then air treat at 500℃ for 6h to obtain ZnO / ZrO2-S5;

[0101] (2) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 40mL of 0.5mg hydrochloric acid dropwise. P A solution of H2PtCl6·6H2O with a concentration of t / mL was stirred for 3 hours, filtered, and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 hours, and then air-treated at 500 °C for 6 hours to obtain the Pt / Al2O3-S5 component.

[0102] (3) 2g of Pt / Al2O3-S5 component and 0.4g of ZnO / ZrO2-S5 were physically ground and treated with pure H2 at 450℃ for 6h to obtain Pt / Al2O3+ZnO / ZrO2-S5 component;

[0103] (4) 0.96 g of Pt / Al2O3+ZnO / ZrO2-S5 was mixed with 1.04 g of ZSM-5 molecular sieve powder and ground to obtain catalyst S5. By mass, the catalyst contained 0.5% Pt, 39.5% alumina, 8% ZnO / ZrO2-S5, and 52% molecular sieve. The molar ratio of Zn and Zr elements on the catalyst surface was determined using XPS, as shown in Table 1.

[0104]

Example 6

[0105] (1) Mix 2g TiO2 and 10g MnO2 in 50mL of deionized water, stir for 6h, filter and wash, and then air treat at 250℃ for 0.5h to obtain TiO2 / MnO2-S6;

[0106] (2) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 40mL of 0.5mg hydrochloric acid dropwise. P A solution of H2PtCl6·6H2O with a concentration of t / mL was stirred for 3 hours, filtered, and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 hours, and then air-treated at 500 °C for 6 hours to obtain the Pt / Al2O3-S6 component.

[0107] (3) 2g of Pt / Al2O3-S6 component and 0.4g of TiO2 / MnO2-S6 were physically ground and treated with pure H2 at 450℃ for 6h to obtain Pt / Al2O3+TiO2 / MnO2-S6 component;

[0108] (4) 0.96 g of Pt / Al2O3+TiO2 / MnO2-S6 was mixed with 1.04 g of ZSM-5 molecular sieve powder and ground to obtain catalyst S6. By mass, the catalyst contained 0.5% Pt, 39.5% alumina, 8% TiO2 / MnO2, and 52% molecular sieve. The molar ratio of Ti and Mn elements on the catalyst surface was determined using XPS characterization, as shown in Table 1.

[0109]

Example 7

[0110] (1) Mix 2g TiO2 and 10g MnO2 in 50mL of deionized water, stir for 6h, filter and wash, and then air treat at 500℃ for 4.5h to obtain TiO2 / MnO2-S7.

[0111] (2) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 40mL of 0.5mg hydrochloric acid dropwise. P A solution of H2PtCl6·6H2O with a concentration of t / mL was stirred for 3 hours, filtered, and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 hours, and then air-treated at 500 °C for 6 hours to obtain the Pt / Al2O3-S7 component.

[0112] (3) 2g of Pt / Al2O3-S7 component and 0.8g of TiO2 / MnO2-S7 were physically ground and treated with pure H2 at 450℃ for 6h to obtain Pt / Al2O3+TiO2 / MnO2-S7 component;

[0113] (4) 0.96 g of Pt / Al2O3+TiO2 / MnO2-S7 was mixed with 1.04 g of ZSM-5 molecular sieve powder and ground to obtain catalyst S7. By mass, the catalyst contained 0.5% Pt, 34% alumina, 13.5% TiO2 / MnO2, and 52% molecular sieve. The molar ratio of Ti and Mn elements on the catalyst surface was determined using XPS characterization, as shown in Table 1.

[0114]

Example 8

[0115] (1) Mix 2g Fe2O3 and 2g WO3 in 50mL of deionized water, stir for 6h, filter and wash, and then air treat at 500℃ for 4.5h to obtain Fe2O3 / WO3-S8;

[0116] (2) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 20mL of 0.5mg hydrochloric acid dropwise. P The solution of H2PdCl6·6H2O with a concentration of d / mL was stirred for 3 h, filtered and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 h, and then air-treated at 500 °C for 6 h to obtain the Pd / Al2O3-S8 component.

[0117] (3) 2g of Pd / Al2O3-S8 component and 1.4g of Fe2O3 / WO3-S8 were physically ground and treated with pure H2 at 450℃ for 6h to obtain Pd / Al2O3+Fe2O3 / WO3-S8 component;

[0118] (4) 1.5g of Pd / Al2O3+Fe2O3 / WO3-S8 was mixed with 0.5g of Beta molecular sieve powder and ground to obtain catalyst S8. By mass, the catalyst contained 0.25% Pd, 43% alumina, 31.75% Fe2O3 / WO3, and 25% molecular sieve. The molar ratio of Fe and W on the catalyst surface was determined by XPS characterization, as shown in Table 1.

[0119]

Example 9

[0120] (1) Mix 2g Co2O3 and 2g MoO3 in 50mL of deionized water, stir for 6h, filter and wash, and then air treat at 500℃ for 4.5h to obtain Co2O3 / MoO3-S9.

[0121] (2) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 25mL of 0.5mg hydrochloric acid dropwise. R The RuCl3 solution was stirred for 3 hours, filtered, and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 hours, and then air-treated at 500 °C for 6 hours to obtain the Ru / Al2O3-9 component.

[0122] (3) 2g Ru / Al2O3-S9 component and 1.4g Co2O3 / MoO3-S9 were physically ground and treated with pure H2 at 450℃ for 6h to obtain Ru / Al2O3+Co2O3 / MoO3-S9 component;

[0123] (4) 1.25g of Ru / Al2O3+Co2O3 / MoO3-S9 was mixed with 0.75g of ZSM-22 molecular sieve powder and ground to obtain catalyst S9. By mass, the catalyst contained 0.20% Ru, 36.5% alumina, 25.8% Co2O3 / MoO3, and 37.5% molecular sieve. The molar ratio of Co and Mo on the catalyst surface was determined by XPS characterization, as shown in Table 1.

[0124]

Example 10

[0125] (1) Mix 0.1g TiO2 and 1.08g MnO2 in 50mL of deionized water, stir for 6h, filter and wash, and then air treat at 500℃ for 6h to obtain TiO2 / MnO2-S10.

[0126] (2) Add 2g of Al2O3 carrier to 100g of deionized water and stir for 1.0h. Then, slowly add hydrochloric acid to adjust the pH to 3.5 and continue stirring for 2.0h. During the stirring process, add 40mL of 0.5mg hydrochloric acid dropwise. P A solution of H2PtCl6·6H2O with a concentration of t / mL was stirred for 3 hours, filtered, and washed with 1.5 L of deionized water. The resulting filter cake was dried in an oven at 100 °C for 12 hours, and then air-treated at 500 °C for 6 hours to obtain the Pt / Al2O3-S10 component.

[0127] (3) 2.0g of Pt / Al2O3-S10 component and 0.6g of TiO2 / MnO2-S10 were physically ground and treated with pure H2 at 450℃ for 6h to obtain Pt / Al2O3+TiO2 / MnO2-S10 component;

[0128] (4) 2.6 g of Pt / Al2O3+TiO2 / MnO2-S10 was mixed with 1.4 g of ZSM-5 molecular sieve powder and ground to obtain catalyst S10. By mass, the catalyst contained 0.5% Pt, 49.5% alumina, 15% TiO2 / MnO2, and 35% molecular sieve. The molar ratio of Ti and Mn elements on the catalyst surface was determined using XPS characterization, as shown in Table 1.

[0129]

Example 11

[0130] The catalysts prepared in Examples 1-10 and Comparative Examples 1-5 were pressed into tablets, sieved through a 20-40 mesh, and 0.3 g of catalyst was placed in a fixed-bed reactor. Under a hydrogen atmosphere, the temperature was increased from room temperature to 450°C at a rate of 10°C / min. After reduction for 2 h, the temperature was lowered to the reaction temperature for catalyst evaluation. The reaction temperature was 200-450°C, the molar ratio of hydrogen to n-hexane was 6.0, and the mass hourly space velocity (WHSV) of n-hexane was 4.5 h⁻¹. 1 The optimal yield of isohexane for each catalyst and the temperature required to achieve the optimal yield are shown in Table 2.

[0131] Table 1 shows the molar ratios of A and B elements on the surface of each catalyst, X, and AOx and BO. y Spatial distance.

[0132] Table 1

[0133]

[0134]

[0135] Table 2 Optimal Catalyst Yield (Y) max ) and the temperature required to achieve the optimal yield (T) max )

[0136] Catalyst number <![CDATA[Y max (%)]]> <![CDATA[T max (℃)]]> D1 46.5 305 D2 49.5 295 D3 55.3 295 D4 50.2 295 D5 53.6 305 S1 72.6 245 S2 70.1 275 S3 75.1 240 S4 75.8 250 S5 74.2 255 S6 68.3 265 S7 72.3 265 S8 70.2 255 S9 68.9 275 S10 67.8 275

[0137] The specific embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. An alkane hydroisomerization catalyst, the catalyst comprising an AO x / BO y component, an M / Al2O3 component, and a molecular sieve component; wherein, AO x / BO y AO x is one or more of TiO2, ZnO, Cr2O3, MgO, Fe2O3, Co2O3, x is a positive integer, BO y is one or more of ZrO2, MnO2, MoO3, WO3, y is a positive integer; M / Al2O3 component M is one or more of Pt, Pd, Rh, Ru, Ir elements; AO x / BO y AO x and BO y The spatial distance is controlled in the range of 20.0-150.0 nm, preferably 20.0-100.5 nm.

2. The catalyst of claim 1, wherein: AO x / BO y The content of the component is 5.0wt%-35.0wt%, the content of the M / Al2O3 component is 20.0wt%-60.0wt%, and the content of the molecular sieve component is 20.0wt%-60.0wt%. Preferably, the content of M in the M / Al203 component is 0.01wt% to 10.0wt% in terms of metal element, preferably 0.1wt% to 2.5wt% in terms of metal element, based on the mass of the catalyst; Preferably, the mass ratio of the oxide AO x / BO y In the composition, the oxide AO x and the oxide BO y is 0.05 to 1.0, preferably 0.2 to 1.

0.

3. The catalyst of claim 1, wherein: The molar ratio X of the surface A element and the surface B element of the catalyst is 0.13 to 0.40, preferably 0.23 to 0.

40.

4. The catalyst of claim 1, wherein: The molecular sieve is selected from at least one of ZSM-5, ZSM-11, ZSM-22, ZSM-35, Beta, MOR, Y, preferably at least one of ZSM-5, ZSM-11, ZSM-22. Preferably, the molecular sieve has a SiO2 / Al2O3 molar ratio of 20 to 250 and a specific surface area of ​​200 to 620 m². 2 / g, pore volume is 0.11~0.92cm 3 / g.

5. A method for preparing an alkane hydroisomerization catalyst, comprising the following steps: (1) mixing AO x , BO y and water, heat treating, to obtain AO x / BO y components; (2) loading a metal M on alumina to obtain an M / Al203 component; (3) mixing the AO component from step (1) with the M / Al2O3 component from step (2) and heat treating to obtain an AO / M / Al2O3 component x / BO y (3) mixing the AO component from step (1) with the M / Al2O3 component from step (2) and heat treating to obtain an AO / M / Al2O3 component x / BO y (3) mixing the AO component from step (1) with the M / Al2O3 component from step (2) and heat treating to obtain an AO / M / Al2O3 component (4) mixing the mixture obtained in step (3) with a molecular sieve to obtain the alkane hydroisomerization catalyst.

6. The method of claim 5, wherein: In step (1), AO x is one or more of TiO2, ZnO, Cr2O3, MgO, Fe2O3, Co2O3, x is a positive integer, BO y is one or more of ZrO2, MnO2, MoO3, WO3, y is a positive integer; and / or, in step (1), the AO x and BO y in a mixing ratio of 0.05 to 1.0, preferably 0.2 to 1.0; In step (1), the heat treatment temperature is 250 to 500°C, preferably 350 to 500°C, and the treatment time is 0.5h to 24h, preferably 4h to 12h.

7. The method of claim 5, wherein: In step (2), the metal M is one or more of Pt, Pd, Rh, Ru, and Ir.

8. The method of claim 5, wherein: In step (3), the mass ratio of AO x / BO y The mass ratio of the component and M / Al203 component is 1:9-7:10; Preferably, in step (3), the heat treatment is carried out under hydrogen atmosphere, preferably, the hydrogen atmosphere has a hydrogen content of 5% to 100%, preferably 50% to 100%. In step (3), the heat treatment is carried out at a temperature of 350 to 500°C, preferably 450 to 500°C, and a treatment time of 0.5h to 24h, preferably 4h to 12h.

9. The method of claim 5, wherein: In step (4), the molecular sieve is selected from at least one of ZSM-5, ZSM-11, ZSM-22, ZSM-35, Beta, MOR, Y, preferably at least one of ZSM-5, ZSM-11, ZSM-22. In step (4), the mass ratio of the mixture obtained in step (3) to the molecular sieve component is 1:9 to 9:

1.

10. Use of the catalyst of any one of claims 1 to 4 or the catalyst prepared by the method of any one of claims 5 to 9 in catalyzing an alkane isomerization reaction.

11. Use according to claim 10, characterized in that: The alkane is at least one of n-alkanes having 4 to 8 carbon atoms; Preferably, the content of M in the M / Al203 component is 0.01wt% to 10.0wt% in terms of metal element, preferably 0.1wt% to 2.5wt% in terms of metal element, based on the mass of the catalyst; And / or, the conditions of the alkane isomerization reaction are: the reaction temperature is 200-405℃, the reaction pressure is 1.0-3.0 MPa, the molar ratio of hydrogen to normal alkane is 1.0-10.0, the mass space velocity of alkane is 1.0-8.0 h -1 .